PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN KEPALA SEKOLAH (STUDI KASUS GURU-GURU SMP NEGERI DI KECAMATAN PATI KABUPATEN PATI) (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to identify and examine  the influence of motivation and work discipline on the teacher’s performance by moderationhead master leadership that takes an objectof primary school teachers in Pati subdistrict Pati Regency. Sampling was done by purposive sampling technique. From the result of purposive sampling, the sample was used in this study, total 179 people. Testing data technique which is used in this study include validity test by factor analysis, reliability test by Cronbach alpha formula, multiple regression analysis, and significance  tests, the coeffisien of determination to prove the hypothesis and moderation regressionanalysis. The result showed that the variables of motivation haspositive and significanteffect of teacher’s performance. Variables of discipline not significanton teacher’s performance.Principal’s leadership haspositiveand significanteffect of teacher’s performance of primary school’s teachers in Pati subdistrict Pati regency. Principal’s leadership can increase work motivation on teacher’s performance, but principal’s leadership can decrease work discipline on teacher’s performance. Key word : motivation, discipline, principal’s leadership, performance